Evaluation of demographic and clinical characteristics of female patients presenting with MINOCA and differences between male patients: A subgroup analysis of MINOCA-TR registry - Gök, Gülay; Çoner, Ali; Çınar, Tufan; Kılıç, Salih; Yenerçağ, Mustafa; Öz, Ahmet; Ekmekçi, Cenk; Özlük, Özlem; Zoghi, Mehdi; Ergene, Asım Oktay; Türk, Uğur Önsel (Aves, 2022)
Objective: Although the prevalence and rate of myocardial infarction with non-obstructive coronary arteries (MINOCA) are higher in women than in men in previous cohorts, potential demographic and clinical differences between women who are diagnosed with MINOCA versus myocardial infarction with obstructive coronary arteries (MIOCA) have not been studied till date. In this study, we aimed to document these characteristics and to compare them between female patients with MINOCA and MIOCA. Methods: The study was a subgroup analysis of the MINO-CA-TR study. The study was a multi-center, observational cohort study that was conducted in Turkey between March 2018 and October 2018. In this study, 477 (29.3%) female patients who had been diagnosed with acute myocardial infarction were evaluated. Results: Of these women, 49 (10.3%) were diagnosed with MINOCA (mean age 58.9 +/- 12.9 years) and 428 (89.7%) had a final diagnosis of MIOCA (mean age 67.4 +/- 11.8 years). The prevalence of hypertension, hyperlipidemia, and diabetes mellitus was significantly lower in the MINOCA group than in the MIOCA group. In addition, the MINOCA group had higher rates of recent flu history and non-ST elevation myocardial infarction (NSTEMI) presentation than the MIOCA group. There were significant clinical differences in patients with MINOCA in terms of sex. The female patients were older, had higher systolic blood pressures, and lower hemoglobin levels than male patients. Conclusion: The study revealed that the prevalence of traditional coronary artery disease risk factors was lower in female patients with MINOCA than in those who had final diagnosis of MIOCA.

Amaç: Daha önceki kohortlarda kadın hastalarda obstrüktif olmayan koroner arterlerle miyokart enfarktüsü (MINOCA) erkeklere göre daha yüksek oranda olmasına rağmen, MINOCA ve obstrüktif koroner arterli miyokart enfarktüsü (MIOCA) tanısı alan kadın hastalar arasındaki potansiyel demografik ve klinik farklılıklar bugüne kadar çalışılmamıştır. Bu çalışma, bu özellikleri araştırmayı ve kadın MINOCA ve MIOCA hastaları arasında karşılaştırmayı amaçladı. Yöntemler: Çalışma, Türk popülasyonu (MINOCA-TR) kayıtlarının subgrup analizidir. Kayıt, Türkiye’de Mart 2018- Ekim 2018 tarihleri arasında yürütülen çok merkezli, gözlemsel bir kohort çalışmasıydı. Bu çalışmada 477 (%29.3) akut miyokart enfarktüsü tanısı alan kadın hasta değerlendirildi. Bulgular: Kadınlardan 49’u (%10.3) MINOCA (ortalama yaş: 58.9±12.9 yıl) ve 428’i (%89.7) MIOCA (ortalama yaş: 67.4±11.8 yıl) tanısı almıştı. MINOCA grubunda hipertansiyon, hiperlipidemi ve diabetes mellitus prevalansları MIOCA grubuna göre anlamlı olarak daha düşüktü. Ek olarak, MINOCA grubunda MIOCA grubuna kıyasla daha yüksek oranlarda yakın zamanlı grip öyküsü ve ST yükselmesiz miyokart enfarktüsü (NSTEMI) prezentasyonu vardı. MINOCA hastalarında cinsiyet açısından önemli klinik farklılıklar vardı. Erkek vakalarla karşılaştırıldığında, kadın hastalar daha yaşlıydı, daha yüksek sistolik kan basıncına ve daha düşük hemoglobin seviyelerine sahipti. Sonuç: Çalışma, MIOCA kesin tanısı almış kadın hastalara göre, kadın MINOCA hastalarında geleneksel koroner arter hastalığı risk faktörünün daha düşük prevalansta olduğunu ortaya koymuştur.
MINOCA ile başvuran kadın hastaların demografik ve klinik özelliklerinin değerlendirilmesi ve erkek hastalarla farklılıkları: MINOCA-TR çalışmasının grup analizi
Keywords: Female; MINOCA; Demographics; Risk Factor